NEW DATA ON THE DIVERSITY OF NOTOUNGULATA (MAMMALIA) FROM FRAY BENTOS FORMATION (LATE OLIGOCENE) IN CORRIENTES PROVINCE, ARGENTINA (Ameghiniana, 2020)
We revise the mammal fossils from the Fray Bentos Formation previously assigned to Notoungulata, as well as some new remains recovered from levels cropping out in Corrientes Province (Argentina). In some cases, previous determinations have been completed to the species level, but others have been substantially modified, identifying different families. At present, identified taxa are: “Prohegetotherium” schiaffinoi (Hegetotheriidae), an undetermined interatheriid that is hypothesized as representing the upper teeth of Eopachyrucos ranchoverdensis, and Argyrohyrax proavus (Interatheriidae), cf. Archaeohyrax suniensis (Archaeohyracidae), cf. Mendozahippus fierensis (“Notohippidae”), a Leontiniidae indet., and some undetermined Notoungulata. The presence of Leontiniidae is based on the specimen CTES-PZ 7871, but those previously assigned to this family are herein discarded as such and reinterpreted (notohippid and undetermined taxon). The Mesotheriidae are discarded among the revised materials, but they are present in the Fray Bentos Formation in Corrientes Province with Trachytherus spegazzinianus (= Ameghinotherium curuzucuatiense). The revised sample presents affinities with the fauna from the type locality of the Fray Bentos Formation, in Uruguay, and the Deseadan assemblages from Quebrada Fiera (Mendoza Province, Argentina), Patagonia (Argentina), and Salla (Bolivia). These similarities are important from a paleobiogeographic point of view, especially by the recognition of cf. M. fierensis, a species only known from Mendoza up to now. Only the finding of new material from Fray Bentos Formation in Corrientes Province will allow us to corroborate these tentative determinations and a possible eastward extension of up-to-now exclusive taxa from Quebrada Fiera.